A copper-based catalyst for synthesizing methanol and a preparation method thereof
By using 13X molecular sieve powder in the copper -based catalyst, the components of copper, zinc, cymbal, and molybdenum ions are added, and phosphoricate is added to solve the problem of poor catalytic activity, low selectivity, and poor thermal stability of the existing copper -based catalyst. It has achieved efficient carbon dioxide conversion and methanol selectivity.
Patent Information
- Application Number
- CN202411686916.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The existing copper-based catalysts for methanol from carbon dioxide hydrogenation have problems such as poor catalytic activity, low selectivity and poor thermal stability.
By using the 13X molecular sieve powder, the four metal ions of copper, zinc, pyrine, and molybdenum, and burning oxidation in the Marve furnace, combined with the addition of phosphate, calcium oxalized, thin water aluminum, and magnesium silicon aluminum, prepare out, and prepare out to prepare out to prepare out to prepare out to prepare out to prepare out to prepare. Copper catalysts with high catalytic activity, methanol selectivity and water stability.
Achieve high catalytic activity, good methanol selectivity, and good thermal stability with carbon dioxide hydrogen alcohol copper alcohol catalysts. The CO2 conversion rate is about 35%, methanol selectivity is more than 95%, and water heat stability reaches more than 96.7%.
Smart Images

Figure CN119175107B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a copper-based catalyst for synthesizing methanol and a preparation method thereof, belonging to the technical field of methanol synthesis. Background Art
[0002] Methanol is an important basic chemical product and a highly potential clean alternative fuel. The cycle mode of producing hydrogen with renewable energy and then using CO2 hydrogenation to synthesize methanol can be used as a solution to the energy shortage problem after the oil and gas era. Therefore, the synthesis of methanol by hydrogenation of carbon dioxide not only achieves the purpose of reducing direct carbon dioxide emissions, but also converts carbon dioxide through chemical reactions, and the methanol produced is used as a chemical raw material and fuel, which has a very broad application prospect. The synthesis of methanol by hydrogenation of CO2 uses synthesis gas rich in CO2 and H2 as raw materials and is carried out using copper-based catalysts. Copper-based catalysts have relatively good catalytic activity, long service life, strong anti-toxicity, relatively low reaction temperature and pressure, etc., but copper-based catalysts currently also have problems such as not particularly ideal catalytic activity (carbon dioxide conversion rate is generally less than 25%), low selectivity (methanol selectivity is less than 70%) and poor stability.
[0003] Chinese patent CN104437510A discloses a method for preparing a copper-zinc-based catalyst for CO2 hydrogenation to methanol. The copper-zinc-based catalyst is prepared by a small-size mixed flow device and ultrasonic assisted action, which can accurately control the catalyst preparation conditions and easily adjust the crystal phase composition of the catalyst active precursor, thereby improving the catalytic performance and hydrothermal stability. The small-size mixed flow device is composed of a mixer and a reaction tube. The catalyst prepared by the method of the present invention can increase the amount of the catalyst active precursor green copper zinc ore, the interaction between copper and zinc is strong, the catalyst metal copper specific surface area is high after reduction, and it has high activity, methanol space-time yield and hydrothermal stability in the CO2 hydrogenation to methanol reaction. The copper-zinc-based catalyst prepared by this patent can only achieve a carbon dioxide conversion rate of up to 33.2%, and the methanol yield is not high. The methanol yield can reach 81% at the beginning, but after heat treatment, the methanol yield drops to 66%, which shows that the thermal stability is not ideal.
[0004] Chinese patent CN117085689A discloses a copper-based catalyst for preparing methanol from carbon dioxide hydrogenation and a preparation method thereof, wherein the preparation method is to use copper source, zinc source and zirconium source or aluminum source as raw materials, sodium carbonate as precipitant, soluble organic compound as carbon source, and adopt coprecipitation-in-situ carbonization-reduction to obtain carbon-modified copper-based catalyst, the components of which include Cu, ZnO, ZrO2 or Al2O3 and C, C is evenly dispersed on the catalyst surface, closely combined with the active component copper, promotes copper dispersion, and obtains high CO2 conversion rate and methanol selectivity. The selectivity of methanol in this patent is relatively high, basically above 80%, but the CO2 conversion rate is not high, reaching only 20.3% at most.
[0005] From the above, we can see that copper-based catalysts for the hydrogenation of carbon dioxide to methanol still have problems such as low CO2 conversion rate, low methanol selectivity and poor thermal stability. Therefore, it is of great practical value to develop copper-based catalysts for the hydrogenation of carbon dioxide to methanol with high catalytic activity, good methanol selectivity and good thermal stability. Summary of the invention
[0006] In view of the deficiencies in the above-mentioned prior art, the present invention provides a copper-based catalyst for synthesizing methanol and a preparation method thereof, so as to achieve the following invention objectives: to prepare a copper-based catalyst for producing methanol by hydrogenation of carbon dioxide with high catalytic activity, good methanol selectivity and good thermal stability.
[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0008] A copper-based catalyst for synthesizing methanol and a preparation method thereof. The copper-based catalyst for synthesizing methanol has initial performance of a CO2 conversion rate of 35.9-36.7%, a methanol selectivity of 95.7-96.4%, and a methanol space-time yield of 1.78-1.85 g / h / mL, and heat-resistant performance of a CO2 conversion rate of 35.1-36.2%, a methanol selectivity of 95.1-95.9%, a methanol space-time yield of 1.74-1.80 g / h / mL, and a hydrothermal stability of 96.7-97.8%.
[0009] The following are further improvements to the above technical solution:
[0010] Step 1: Impregnation Load
[0011] Put the 13X molecular sieve powder into an impregnation kettle, then add a mixed aqueous solution of copper nitrate, zinc nitrate, bismuth nitrate and molybdenum nitrate until the mixed aqueous solution just immerses the 13X molecular sieve powder, and after standing and impregnating for 15 to 20 hours, start stirring, control the stirring rate at 150 to 500 rpm, stir for 25 to 40 minutes, stop stirring, continue to stand and impregnate for 15 to 20 hours, then filter the material, put the filtered solid into a muffle furnace, and keep it at 220 to 260° C. for 8 to 15 hours to obtain a 13X molecular sieve powder loaded with copper, zinc, bismuth and molybdenum;
[0012] The particle size of the 13X molecular sieve powder is 1-8 μm, and the internal pore size is 0.3-0.6 nm;
[0013] The mixed aqueous solution of copper nitrate, zinc nitrate, bismuth nitrate and molybdenum nitrate, wherein the mass ratio of copper nitrate, zinc nitrate, bismuth nitrate, molybdenum nitrate and deionized water is 30-70:10-40:4-15:1-10:150-250.
[0014] Step 2: Slurry preparation
[0015] 13X molecular sieve powder loaded with copper, zinc, bismuth and molybdenum, zirconium phosphate, calcium oxalate powder, pseudo-boehmite and deionized water are added into a double planetary mixer, and the stirring rate is controlled at 100-150 rpm and the dispersion rate is 5000-9000 rpm. After stirring and dispersing for 4-7 hours, magnesium aluminum silicate is added, and stirring and dispersing is continued for 3-6 hours. Then, the dispersion is stopped, and the negative pressure in the stirring kettle is evacuated and maintained at -0.096-0.088 MPa. The stirring rate is controlled at 80-120 rpm for degassing. After continuous stirring and degassing for 5-12 hours, a viscous slurry like toothpaste is obtained;
[0016] The zirconium phosphate is in powder form with a particle size of 30 to 800 nm;
[0017] The particle size of the calcium oxalate powder is 0.01-0.6 μm;
[0018] The particle size of the pseudo-boehmite is 10-500 nm;
[0019] The particle size of the magnesium aluminum silicate is 0.1-2 μm;
[0020] The feeding mass ratio of the 13X molecular sieve powder loaded with copper, zinc, bismuth and molybdenum, zirconium phosphate, calcium oxalate powder, pseudo-boehmite, deionized water and magnesium aluminum silicate is 55-95:5-12:5-11:9-16:80-130:1-5.
[0021] Step 3: Extrusion
[0022] The slurry was injected into the extruder, and the screw speed and the diameter of the die of the die head were adjusted so that the diameter of the extruded nearly round particles was 3-11 mm to obtain the copper-based catalyst original particles.
[0023] Step 4: Curing and calcining
[0024] The copper-based catalyst original particles are placed in an environment with a relative humidity of 50% at room temperature for 18 to 28 hours, and after natural drying, are placed in a muffle furnace and heated from room temperature to 100 to 140°C at a heating rate of 0.5 to 2.5°C / min. After constant temperature curing for 5 to 10 hours, the temperature is then increased to 360 to 450°C at a heating rate of 1 to 3°C / min, and constant temperature calcined for 12 to 18 hours. Then, the particles are naturally cooled to room temperature to obtain a cured and calcined copper-based catalyst.
[0025] Step 5: Secondary impregnation loading
[0026] The solidified calcined copper-based catalyst is placed in an impregnation kettle, and then a mixed aqueous solution of copper nitrate, zinc nitrate, bismuth nitrate and molybdenum nitrate is added until the mixed aqueous solution just immerses the solidified calcined copper-based catalyst, and after standing and impregnating for 15 to 20 hours, stirring is started, and stirring is controlled at a stirring rate of 150 to 500 rpm for 25 to 40 minutes, and stirring is stopped, and the standing and impregnation is continued for 15 to 20 hours, and then the material is discharged and filtered, and the filtered solid is placed in a muffle furnace, and after being kept warm at 220 to 260° C. for 8 to 15 hours, a secondary impregnation-loaded copper-based catalyst is obtained;
[0027] The mixed aqueous solution of copper nitrate, zinc nitrate, bismuth nitrate and molybdenum nitrate, wherein the mass ratio of copper nitrate, zinc nitrate, bismuth nitrate, molybdenum nitrate and deionized water is 30-70:10-40:4-15:1-10:150-250.
[0028] Step 6: Secondary calcination
[0029] The copper-based catalyst loaded with secondary impregnation is placed in a muffle furnace, and then heated to 360-450°C at a heating rate of 1-3°C / min. After constant temperature roasting for 12-18 hours, it is naturally cooled to room temperature to obtain a finished copper-based catalyst for synthesizing methanol.
[0030] Compared with the prior art, the present invention achieves the following beneficial effects:
[0031] 1. The present invention uses 13X molecular sieve powder to impregnate and load four metal ions of copper, zinc, bismuth and molybdenum, and then after burning and oxidation in a muffle furnace, the hole walls and outer surfaces of the internal holes of the 13X molecular sieve powder are attached with the oxides of the above four metals, wherein the oxides of copper and zinc play the role of main catalysts, and the oxides of bismuth and molybdenum mainly play the role of co-catalysts. The oxides of bismuth and molybdenum have strong alkalinity and can enhance the adsorption of carbon dioxide and increase the conversion rate of carbon dioxide. Moreover, during the impregnation loading process, the bismuth and molybdenum metal ions have a greater repulsion effect on copper ions and zinc ions because the ions have more peripheral charges and a larger charge density, which can promote the dispersion of copper ions and zinc ions during the impregnation adsorption process. In the process, copper ions and zinc ions will also avoid forming large oxide crystals due to their good dispersion, thus ensuring the specific surface area of copper and zinc oxides and increasing the catalytic reaction active points on the catalyst surface to ensure that the catalyst has better methanol selectivity. In addition, molybdenum oxide can also enhance the hydrothermal stability of the catalyst. Moreover, 13X molecular sieve powder itself is an alkaline substance and has a natural adsorption effect on acidic oxides such as carbon dioxide. Therefore, using 13X molecular sieve powder as a carrier of metal catalytic active substances can effectively capture and adsorb carbon dioxide as a reaction raw material, thereby increasing the concentration of reactants and promoting the carbon dioxide hydrogenation to synthesize methanol reaction to be easier to proceed in the positive reaction direction, thereby ensuring that carbon dioxide has a relatively high conversion rate and a relatively high methanol selectivity in the reaction process;
[0032] 2. The zirconium phosphate added in the present invention has excellent thermal stability. The layered structure of zirconium phosphate itself has a very strong charge stabilizing effect and medium- and long-range lattice adsorption effect on copper, zinc, bismuth, and molybdenum oxides. Therefore, the addition of zirconium phosphate can greatly improve the hydrothermal stability of copper-based catalysts.
[0033] 3. The calcium oxalate powder added in the present invention has a particle size in the range of 0.01 to 0.6 μm, which is a submicron-level ultrafine powder. In the slurry preparation process, these ultrafine calcium oxalate powders are evenly dispersed into the slurry through the strong stirring and dispersing action of the double planetary mixer, and then extruded and formed, and then very evenly distributed in the original particles of the copper-based catalyst. In the curing and roasting stage, calcium oxalate slowly decomposes and forms a fine microporous structure inside the copper-based catalyst, which increases the specific surface area of the copper-based catalyst and increases the adsorption amount of copper, zinc, bismuth and molybdenum by the catalyst carrier during the secondary impregnation process, thereby improving the catalytic performance of the final catalyst product;
[0034] 4. The present invention adds pseudo-boehmite, and utilizes the property of pseudo-boehmite to form sol to bond various powdery substances in the slurry, so that each powder component of the catalyst can be formed into solid spherical particles. Pseudo-boehmite itself is an alkaline substance, and the aluminum oxide formed after roasting has very excellent high temperature resistance, which can enhance the temperature resistance of the catalyst itself. In addition, in order to adjust the thixotropic fluidity of pseudo-boehmite after forming sol and promote the smooth progress of the extrusion molding process, an inorganic thickening thixotropic agent magnesium aluminum silicate is selected to improve the material fluidity in the slurry preparation process to facilitate the uniform dispersion of the powder material. Magnesium aluminum silicate will also increase the static viscosity of the slurry after extrusion molding, which is conducive to the original copper-based catalyst particles that have not fully reached a high strength during the curing roasting process to maintain a good spherical state;
[0035] 5. The present invention further increases the loading amount of the catalyst active components through the secondary impregnation loading and secondary calcination steps, thereby making the copper-based catalyst finished product have very high catalytic activity;
[0036] 6. The copper-based catalyst for synthesizing methanol obtained by the present invention has initial performance: CO2 conversion rate 35.9~36.7%, methanol selectivity 95.7~96.4%, methanol space-time yield 1.78~1.85g / h / mL, and heat-resistant performance: CO2 conversion rate 35.1~36.2%, methanol selectivity 95.1~95.9%, methanol space-time yield 1.74~1.80g / h / mL, and hydrothermal stability 96.7~97.8%. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a scanning electron microscope photograph of the cross section of the copper-based catalyst for synthesizing methanol obtained in Example 1, magnified 10,000 times;
[0038] Figure 2 This is a scanning electron microscope photograph of the cross section of the copper-based catalyst for synthesizing methanol obtained in Example 2, magnified 10,000 times;
[0039] Figure 3 The copper-based catalyst for synthesizing methanol obtained in Example 1 has an XRD spectrum measured after being pressed into powder. DETAILED DESCRIPTION
[0040] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0041] Example 1: A method for preparing a copper-based catalyst for synthesizing methanol
[0042] Step 1: Impregnation Load
[0043] Put the 13X molecular sieve powder into an impregnation kettle, then add a mixed aqueous solution of copper nitrate, zinc nitrate, bismuth nitrate and molybdenum nitrate until the mixed aqueous solution just immerses the 13X molecular sieve powder, and after standing and impregnating for 18 hours, start stirring, control the stirring rate at 450 rpm, stir for 30 minutes, stop stirring, continue to stand and impregnate for 18 hours, then filter the material, put the filtered solid into a muffle furnace, and after keeping warm at 250° C. for 13 hours, obtain a 13X molecular sieve powder loaded with copper, zinc, bismuth and molybdenum;
[0044] The particle size of the 13X molecular sieve powder is 3 μm, and the internal pore size is 0.4 nm;
[0045] The mixed aqueous solution of copper nitrate, zinc nitrate, bismuth nitrate and molybdenum nitrate, wherein the mass ratio of copper nitrate, zinc nitrate, bismuth nitrate, molybdenum nitrate and deionized water is 50:30:10:5:210.
[0046] Step 2: Slurry preparation
[0047] 13X molecular sieve powder loaded with copper, zinc, bismuth and molybdenum, zirconium phosphate, calcium oxalate powder, pseudo-boehmite and deionized water were added into a double planetary mixer, and the stirring rate was controlled at 140 rpm and the dispersion rate was 8000 rpm. After stirring and dispersing for 6 hours, magnesium aluminum silicate was added, and stirring and dispersing was continued for 5 hours. Then, the dispersion was stopped, and the negative pressure in the stirring kettle was evacuated and maintained at -0.092 MPa. The stirring rate was controlled at 110 rpm to discharge bubbles. After continuous stirring and dispersing for 10 hours, a viscous slurry like toothpaste was obtained.
[0048] The zirconium phosphate is in powder form with a particle size of 80 nm;
[0049] The particle size of the calcium oxalate powder is 0.2 μm;
[0050] The particle size of the pseudo-boehmite is 100 nm;
[0051] The particle size of the magnesium aluminum silicate is 0.5 μm;
[0052] The mass ratio of the 13X molecular sieve powder loaded with copper, zinc, bismuth and molybdenum, zirconium phosphate, calcium oxalate powder, pseudo-boehmite, deionized water and magnesium aluminum silicate is 70:8:9:11:110:4.
[0053] Step 3: Extrusion
[0054] The slurry was injected into the extruder, and the screw speed and the diameter of the die of the die head were adjusted so that the diameter of the extruded nearly round particles was 6 mm, thereby obtaining the copper-based catalyst original particles.
[0055] Step 4: Curing and calcining
[0056] The copper-based catalyst original particles were placed in an environment with a relative humidity of 50% at room temperature for 22 hours. After natural drying, they were placed in a muffle furnace and heated from room temperature to 130°C at a heating rate of 1°C / min. After constant temperature curing for 7 hours, they were then heated to 400°C at a heating rate of 2°C / min, calcined at a constant temperature for 15 hours, and then naturally cooled to room temperature to obtain a cured and calcined copper-based catalyst.
[0057] Step 5: Secondary impregnation loading
[0058] The solidified and calcined copper-based catalyst is placed in an impregnation kettle, and then a mixed aqueous solution of copper nitrate, zinc nitrate, bismuth nitrate and molybdenum nitrate is added until the mixed aqueous solution just immerses the solidified and calcined copper-based catalyst. After standing and impregnating for 18 hours, stirring is started, and stirring is controlled at a stirring rate of 450 rpm for 30 minutes. Stirring is stopped, and the standing and impregnation is continued for 18 hours. The material is then discharged and filtered, and the filtered solid is placed in a muffle furnace. After being kept warm at 250° C. for 13 hours, a secondary impregnation-loaded copper-based catalyst is obtained.
[0059] The mixed aqueous solution of copper nitrate, zinc nitrate, bismuth nitrate and molybdenum nitrate, wherein the mass ratio of copper nitrate, zinc nitrate, bismuth nitrate, molybdenum nitrate and deionized water is 50:30:10:5:210.
[0060] Step 6: Secondary calcination
[0061] The copper-based catalyst loaded with secondary impregnation was placed in a muffle furnace, and then heated to 400°C at a heating rate of 2°C / min. After constant temperature calcination for 15 hours, it was naturally cooled to room temperature to obtain a finished copper-based catalyst for synthesizing methanol.
[0062] Example 2: A method for preparing a copper-based catalyst for synthesizing methanol
[0063] Step 1: Impregnation Load
[0064] Put the 13X molecular sieve powder into an impregnation kettle, then add a mixed aqueous solution of copper nitrate, zinc nitrate, bismuth nitrate and molybdenum nitrate until the mixed aqueous solution just immerses the 13X molecular sieve powder, and after standing and impregnating for 15 hours, start stirring, control the stirring rate at 150 rpm, stir for 25 minutes, stop stirring, continue to stand and impregnate for 15 hours, then filter the material, put the filtered solid into a muffle furnace, and after keeping warm at 220° C. for 8 hours, obtain a 13X molecular sieve powder loaded with copper, zinc, bismuth and molybdenum;
[0065] The particle size of the 13X molecular sieve powder is 1 μm, and the internal pore size is 0.3 nm;
[0066] The mixed aqueous solution of copper nitrate, zinc nitrate, bismuth nitrate and molybdenum nitrate, wherein the mass ratio of copper nitrate, zinc nitrate, bismuth nitrate, molybdenum nitrate and deionized water is 30:10:4:1:150.
[0067] Step 2: Slurry preparation
[0068] 13X molecular sieve powder loaded with copper, zinc, bismuth and molybdenum, zirconium phosphate, calcium oxalate powder, pseudo-boehmite and deionized water were added into a double planetary mixer, and the stirring rate was controlled at 100 rpm and the dispersion rate was 5000 rpm. After stirring and dispersing for 4 hours, magnesium aluminum silicate was added, and the stirring and dispersing was continued for 3 hours. After that, the dispersion was stopped, and the negative pressure in the stirring kettle was evacuated and maintained at -0.096 MPa. The stirring rate was controlled at 80 rpm to discharge bubbles. After continuous stirring and dispersing for 5 hours, a viscous slurry like toothpaste was obtained.
[0069] The zirconium phosphate is in powder form with a particle size of 30 nm;
[0070] The particle size of the calcium oxalate powder is 0.01 μm;
[0071] The particle size of the pseudo-boehmite is 10 nm;
[0072] The particle size of the magnesium aluminum silicate is 0.1 μm;
[0073] The mass ratio of the 13X molecular sieve powder loaded with copper, zinc, bismuth and molybdenum, zirconium phosphate, calcium oxalate powder, pseudo-boehmite, deionized water and magnesium aluminum silicate is 55:5:5:9:80:1.
[0074] Step 3: Extrusion
[0075] The slurry was injected into the extruder, and the screw speed and the diameter of the die of the die head were adjusted so that the diameter of the extruded nearly round particles was 3 mm, thereby obtaining the original copper-based catalyst particles.
[0076] Step 4: Curing and calcining
[0077] The copper-based catalyst original particles were placed in an environment with a relative humidity of 50% at room temperature for 18 hours, and after natural drying, they were placed in a muffle furnace and heated from room temperature to 100°C at a heating rate of 0.5°C / min. After constant temperature curing for 5 hours, the temperature was then increased to 360°C at a heating rate of 1°C / min, and constant temperature calcined for 12 hours. Then, they were naturally cooled to room temperature to obtain a cured and calcined copper-based catalyst.
[0078] Step 5: Secondary impregnation loading
[0079] The solidified calcined copper-based catalyst is placed in an impregnation kettle, and then a mixed aqueous solution of copper nitrate, zinc nitrate, bismuth nitrate and molybdenum nitrate is added until the mixed aqueous solution just immerses the solidified calcined copper-based catalyst, and after standing and impregnating for 15 hours, stirring is started, and stirring is controlled at a stirring rate of 150 rpm for 25 minutes, and stirring is stopped, and the standing and impregnation is continued for 15 hours, and then the material is discharged and filtered, and the filtered solid is placed in a muffle furnace, and after being kept warm at 220° C. for 8 hours, a secondary impregnation-loaded copper-based catalyst is obtained;
[0080] The mixed aqueous solution of copper nitrate, zinc nitrate, bismuth nitrate and molybdenum nitrate, wherein the mass ratio of copper nitrate, zinc nitrate, bismuth nitrate, molybdenum nitrate and deionized water is 30:10:4:1:150.
[0081] Step 6: Secondary calcination
[0082] The copper-based catalyst loaded with secondary impregnation was placed in a muffle furnace, and then heated to 360°C at a heating rate of 1°C / min. After constant temperature roasting for 12 hours, it was naturally cooled to room temperature to obtain a finished copper-based catalyst for synthesizing methanol.
[0083] Example 3: A method for preparing a copper-based catalyst for synthesizing methanol
[0084] Step 1: Impregnation Load
[0085] Put the 13X molecular sieve powder into an impregnation kettle, then add a mixed aqueous solution of copper nitrate, zinc nitrate, bismuth nitrate and molybdenum nitrate until the mixed aqueous solution just immerses the 13X molecular sieve powder, and after standing and impregnating for 20 hours, start stirring, control the stirring rate at 500 rpm, stir for 40 minutes, stop stirring, continue to stand and impregnate for 20 hours, then filter the material, put the filtered solid into a muffle furnace, and keep it at 260° C. for 15 hours to obtain a 13X molecular sieve powder loaded with copper, zinc, bismuth and molybdenum;
[0086] The particle size of the 13X molecular sieve powder is 8 μm, and the internal pore size is 0.6 nm;
[0087] The mixed aqueous solution of copper nitrate, zinc nitrate, bismuth nitrate and molybdenum nitrate, wherein the mass ratio of copper nitrate, zinc nitrate, bismuth nitrate, molybdenum nitrate and deionized water is 70:40:15:10:250.
[0088] Step 2: Slurry preparation
[0089] 13X molecular sieve powder loaded with copper, zinc, bismuth and molybdenum, zirconium phosphate, calcium oxalate powder, pseudo-boehmite and deionized water were added into a double planetary mixer, and the stirring rate was controlled at 150 rpm and the dispersion rate was 9000 rpm. After stirring and dispersing for 7 hours, magnesium aluminum silicate was added, and stirring and dispersing was continued for 6 hours. Then, dispersion was stopped, vacuum was drawn and the negative pressure in the stirring kettle was maintained at -0.088 MPa, and the stirring rate was controlled at 120 rpm to discharge bubbles. After continuous stirring and dispersing for 12 hours, a viscous slurry like toothpaste was obtained;
[0090] The zirconium phosphate is in powder form with a particle size of 800 nm;
[0091] The particle size of the calcium oxalate powder is 0.6 μm;
[0092] The particle size of the pseudo-boehmite is 500 nm;
[0093] The particle size of the magnesium aluminum silicate is 2 μm;
[0094] The mass ratio of the 13X molecular sieve powder loaded with copper, zinc, bismuth and molybdenum, zirconium phosphate, calcium oxalate powder, pseudo-boehmite, deionized water and magnesium aluminum silicate is 95:12:11:16:130:5.
[0095] Step 3: Extrusion
[0096] The slurry was injected into the extruder, and the screw speed and the diameter of the die of the die head were adjusted so that the diameter of the extruded nearly round particles was 11 mm, thereby obtaining the copper-based catalyst original particles.
[0097] Step 4: Curing and calcining
[0098] The copper-based catalyst original particles were placed in an environment with a relative humidity of 50% at room temperature for 28 hours. After natural drying, they were placed in a muffle furnace and heated from room temperature to 140°C at a heating rate of 2.5°C / min. After constant temperature curing for 10 hours, they were then heated to 450°C at a heating rate of 3°C / min, calcined at a constant temperature for 18 hours, and then naturally cooled to room temperature to obtain a cured and calcined copper-based catalyst.
[0099] Step 5: Secondary impregnation loading
[0100] The solidified calcined copper-based catalyst is placed in an impregnation kettle, and then a mixed aqueous solution of copper nitrate, zinc nitrate, bismuth nitrate and molybdenum nitrate is added until the mixed aqueous solution just immerses the solidified calcined copper-based catalyst, and after standing and impregnating for 20 hours, stirring is started, and stirring is carried out for 40 minutes under the condition of controlling the stirring rate to 500 rpm, and stirring is stopped, and the standing and impregnation is continued for 20 hours, and then the material is discharged and filtered, and the filtered solid is placed in a muffle furnace, and after being kept warm at 260° C. for 15 hours, a secondary impregnation-loaded copper-based catalyst is obtained;
[0101] The mixed aqueous solution of copper nitrate, zinc nitrate, bismuth nitrate and molybdenum nitrate, wherein the mass ratio of copper nitrate, zinc nitrate, bismuth nitrate, molybdenum nitrate and deionized water is 70:40:15:10:250.
[0102] Step 6: Secondary calcination
[0103] The copper-based catalyst loaded with secondary impregnation was placed in a muffle furnace, and then heated to 450°C at a heating rate of 3°C / min. After constant temperature roasting for 18 hours, it was naturally cooled to room temperature to obtain a finished copper-based catalyst for synthesizing methanol.
[0104] Comparative Example 1: Based on Example 1, in step 1, impregnation loading and step 5, secondary impregnation loading, no bismuth nitrate is added to the mixed aqueous solution, and 10 parts of bismuth nitrate are replaced by 10 parts of copper nitrate. The specific operation is as follows:
[0105] Step 1: Impregnation Load
[0106] In the mixed aqueous solution of copper nitrate, zinc nitrate, bismuth nitrate and molybdenum nitrate, 10 parts of bismuth nitrate were replaced by 10 parts of copper nitrate, and the other operations were the same as in Example 1;
[0107] The operations of steps 2, 3, and 4 are the same as those of Example 1;
[0108] Step 5: Secondary impregnation loading
[0109] In the mixed aqueous solution of copper nitrate, zinc nitrate, bismuth nitrate and molybdenum nitrate, 10 parts of bismuth nitrate were replaced by 10 parts of copper nitrate, and the other operations were the same as in Example 1;
[0110] The operation of step 6 is the same as that of embodiment 1.
[0111] Comparative Example 2: Based on Example 1, in step 1, impregnation loading and step 5, secondary impregnation loading, no molybdenum nitrate is added to the mixed aqueous solution, and 5 parts of molybdenum nitrate are replaced by 5 parts of copper nitrate. The specific operation is as follows:
[0112] Step 1: Impregnation Load
[0113] In the mixed aqueous solution of copper nitrate, zinc nitrate, bismuth nitrate and molybdenum nitrate, 5 parts of molybdenum nitrate are replaced by 5 parts of copper nitrate, and the other operations are the same as in Example 1;
[0114] The operations of steps 2, 3, and 4 are the same as those of Example 1;
[0115] Step 5: Secondary impregnation loading
[0116] In the mixed aqueous solution of copper nitrate, zinc nitrate, bismuth nitrate and molybdenum nitrate, 5 parts of molybdenum nitrate are replaced by 5 parts of copper nitrate, and the other operations are the same as in Example 1;
[0117] The operation of step 6 is the same as that of embodiment 1.
[0118] Comparative Example 3: Based on Example 1, in step 2, in the slurry preparation, no zirconium phosphate was added, and 8 parts of zirconium phosphate were replaced by 8 parts of 13X molecular sieve powder loaded with copper, zinc, bismuth and molybdenum. The specific operation was as follows:
[0119] Step 1: The operation is the same as in Example 1;
[0120] Step 2: Slurry preparation
[0121] 8 parts of zirconium phosphate were replaced by 8 parts of 13X molecular sieve powder loaded with copper, zinc, bismuth and molybdenum, and the other operations were the same as in Example 1;
[0122] The operations of steps 3, 4, 5 and 6 are the same as those of Example 1.
[0123] Comparative Example 4: Based on Example 1, in step 2, in the slurry preparation, no calcium oxalate powder was added, and 9 parts of calcium oxalate powder were replaced by 9 parts of 13X molecular sieve powder loaded with copper, zinc, bismuth and molybdenum. The specific operation was as follows:
[0124] Step 1: The operation is the same as in Example 1;
[0125] Step 2: Slurry preparation
[0126] 9 parts of calcium oxalate powder were replaced by 9 parts of 13X molecular sieve powder loaded with copper, zinc, bismuth and molybdenum, and the other operations were the same as in Example 1;
[0127] The operations of steps 3, 4, 5 and 6 are the same as those of Example 1.
[0128] Comparative Example 5: Based on Example 1, in step 2, in the slurry preparation, magnesium aluminum silicate was not added, and 4 parts of magnesium aluminum silicate were replaced by 4 parts of 13X molecular sieve powder loaded with copper, zinc, bismuth and molybdenum. The specific operation was as follows:
[0129] Step 1: The operation is the same as in Example 1;
[0130] Step 2: Slurry preparation
[0131] The 4 parts of magnesium aluminum silicate were replaced by 4 parts of 13X molecular sieve powder loaded with copper, zinc, bismuth and molybdenum, and the other operations were the same as in Example 1;
[0132] The operations of steps 3, 4, 5 and 6 are the same as those of Example 1.
[0133] Comparative Example 6: Based on Example 1, step 5, secondary impregnation loading and step 6, secondary calcination are not performed, and the copper-based catalyst product for synthesizing methanol is directly obtained after step 4, curing and calcination. The specific operation is as follows:
[0134] The operations of steps 1, 2, and 3 are the same as those of Example 1;
[0135] Step 4: Curing and calcining
[0136] The copper-based catalyst original particles were placed in an environment with a relative humidity of 50% at room temperature for 22 hours, and after natural drying, they were placed in a muffle furnace and heated from room temperature to 130°C at a heating rate of 1°C / min. After constant temperature curing for 7 hours, they were then heated to 400°C at a heating rate of 2°C / min, calcined at a constant temperature for 15 hours, and then naturally cooled to room temperature to obtain a finished copper-based catalyst for synthesizing methanol.
[0137] Performance Test:
[0138] The catalytic activity of the copper-based catalysts for methanol synthesis obtained in Examples 1, 2, 3 and Comparative Examples 1, 2, 3, 4, 5, and 6 was tested. The test method was as follows: the activity of the catalyst was evaluated in a micro fixed bed reactor. The loading amount of the copper-based catalyst was 2 mL. Before use, the catalyst was in situ reduced in the reactor with a H2 / N2 mixed gas containing 5% H2. The final reduction temperature was 240°C. The raw gas composition was H2 / CO2=3 / 1 (volume ratio), the reaction pressure was 3 MPa, and the space velocity was 1×10 4 h -1 The evaluation temperature is 220℃, and the result after the reaction is stable for 4 hours is the initial performance. Then the catalyst is heat-resistant for 5 hours at 350℃ under N2-H2O atmosphere (bubbling 100℃ water with N2), normal pressure, and then restored to the above activity evaluation conditions. The result after stabilization for 2 hours is called the post-heat-resistant performance. The product is analyzed by gas chromatography, and the evaluation results are shown in Table 1, where hydrothermal stability = methanol yield 耐热后 / Methanol yield 初始 ×100%, see Table 1 for specific test results:
[0139] Table 1
[0140]
[0141] From the data in Table 1, it can be seen that the initial performance and heat-resistant performance of the copper-based catalysts obtained in Examples 1, 2, and 3, the CO2 conversion rate is all above 35%, the methanol selectivity is also above 95%, the methanol space-time yield is greater than 1.74 g / h / mL, and the hydrothermal stability can reach above 96.7%, which shows that the copper-based catalyst prepared by the present invention has the performance advantages of high catalytic activity, good methanol selectivity and good thermal stability; in Comparative Example 1 without adding bismuth nitrate, the copper-based catalyst finally obtained will not be loaded with bismuth oxide, and in Comparative Example 1 without bismuth oxide, the CO2 conversion rate is reduced to 28.5% and 27.6%, the methanol selectivity is reduced to 87.4% and 86.3%, the methanol space-time yield is reduced to 1.45 g / h / mL and 1.38 g / h / mL, and the hydrothermal stability is slightly reduced to 95.2%, it can be seen that the addition of bismuth element can effectively improve the catalytic activity and methanol selectivity of the copper-based catalyst, and bismuth element has no obvious negative impact on hydrothermal stability; in Comparative Example 2 without adding platinum nitrate, the situation is similar to that in Comparative Example 1, except that the CO2 conversion rate, methanol selectivity and methanol space-time yield of Comparative Example 2, the degree of decrease in these three performance indicators is less than that in Comparative Example 1, and the magnitude of the decrease in hydrothermal stability is greater than that in Comparative Example 1. It can be seen that the molybdenum oxide formed after the addition of molybdenum element has a very significant effect on improving the catalytic activity and methanol selectivity of the copper-based catalyst, and molybdenum element has a certain effect on improving the hydrothermal stability of the copper-based catalyst; in Comparative Example 3, zirconium phosphate is not added. Compared with Example 1, the catalytic activity and methanol selectivity of Comparative Example 3 are not greatly reduced, but the hydrothermal stability of Comparative Example 3 is reduced to the lowest value among all embodiments and comparative examples, which indicates that zirconium phosphate can mainly play a role in improving the hydrothermal stability of the copper-based catalyst; in Comparative Example 4, calcium oxalate powder is not added, the catalytic activity and methanol selectivity of Comparative Example 4 are sharply reduced, and the hydrothermal stability is basically unchanged, which indicates that the addition of calcium oxalate is effective in improving the catalytic activity and methanol selectivity of the copper-based catalyst. The selectivity plays a vital role, which may be due to the pore-forming effect of the thermal decomposition of calcium oxalate, which can increase the specific surface area of the catalyst carrier, and then greatly increase the loading amount of the metal active substance, so that the final catalyst product has better catalytic performance; in Example 5, magnesium aluminum silicate is not added, and the catalytic activity and methanol selectivity are significantly reduced, and the hydrothermal stability is also significantly reduced. Magnesium aluminum silicate is a thixotropic thickener, which has a great influence on the preparation of slurry and extrusion molding. This shows that without adding magnesium aluminum silicate, the uniformity of the slurry during the preparation of the slurry and the catalyst during the extrusion molding process are improved. The macroscopic and microscopic structures of the catalyst will be greatly negatively affected, which in turn affects the catalytic performance of the copper-based catalyst; in Comparative Example 6, which does not perform the secondary impregnation loading and secondary calcination steps, the catalytic activity and methanol space-time yield are reduced to the lowest values among all the embodiments and comparative examples, and the hydrothermal stability does not change, which shows that secondary impregnation loading and secondary calcination play an extremely important role in increasing the loading amount of metal active substances on the catalyst carrier. The secondary impregnation loading and secondary calcination can significantly increase the loading amount of the active substances of the copper-based catalyst, thereby greatly improving the overall catalytic activity of the catalyst. .
[0142] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a copper-based catalyst for preparing methanol by hydrogenating carbon dioxide, characterized in that: The preparation method of the copper-based catalyst comprises six steps: impregnation loading, slurry preparation, extrusion molding, curing and calcining, secondary impregnation loading, and secondary calcining; The impregnation loading is to put the 13X molecular sieve powder into an impregnation kettle, and then add a mixed aqueous solution of copper nitrate, zinc nitrate, bismuth nitrate and molybdenum nitrate until the mixed aqueous solution just immerses the 13X molecular sieve powder, and after standing and impregnating for 15 to 20 hours, start stirring, control the stirring rate at 150 to 500 rpm, stir for 25 to 40 minutes, stop stirring, continue to stand and impregnate for 15 to 20 hours, then filter the discharged material, put the filtered solid into a muffle furnace, and keep it at 220 to 260° C. for 8 to 15 hours to obtain a 13X molecular sieve powder loaded with copper, zinc, bismuth and molybdenum; The slurry is prepared by adding 13X molecular sieve powder loaded with copper, zinc, bismuth and molybdenum, zirconium phosphate, calcium oxalate powder, pseudo-boehmite and deionized water into a double planetary mixer, controlling the stirring rate at 100-150 rpm and the dispersion rate at 5000-9000 rpm, stirring and dispersing for 4-7 hours, then adding magnesium aluminum silicate, continuing to stir and disperse for 3-6 hours, stopping the dispersion, evacuating and maintaining the negative pressure in the stirring kettle at -0.096-0.088 MPa, controlling the stirring rate at 80-120 rpm to discharge bubbles, and continuing to stir and discharge bubbles for 5-12 hours to obtain a viscous slurry; The extrusion molding comprises injecting the slurry into the extruder, adjusting the screw speed and the diameter of the die of the die head so that the diameter of the extruded nearly round particles is 3-11 mm, and obtaining the original particles of the copper-based catalyst; The curing and calcining comprises placing the original copper-based catalyst particles in an environment with a relative humidity of 50% at room temperature for 18 to 28 hours, naturally drying them, placing them in a muffle furnace, heating them from room temperature to 100 to 140° C. at a heating rate of 0.5 to 2.5° C. / min, curing them at a constant temperature for 5 to 10 hours, then heating them to 360 to 450° C. at a heating rate of 1 to 3° C. / min, calcining them at a constant temperature for 12 to 18 hours, and then naturally cooling them to room temperature to obtain the copper-based catalyst after curing and calcining; The secondary impregnation loading comprises placing the solidified calcined copper-based catalyst into an impregnation kettle, then adding a mixed aqueous solution of copper nitrate, zinc nitrate, bismuth nitrate and molybdenum nitrate until the mixed aqueous solution just immerses the solidified calcined copper-based catalyst, and standing and impregnating for 15 to 20 hours, starting stirring, stirring for 25 to 40 minutes under the condition of controlling the stirring rate at 150 to 500 rpm, stopping stirring, and continuing to stand and impregnate for 15 to 20 hours, then filtering the discharged material, placing the filtered solid into a muffle furnace, and keeping the temperature at 220 to 260° C. for 8 to 15 hours to obtain a secondary impregnation loaded copper-based catalyst; The secondary calcination is to place the secondary impregnated loaded copper-based catalyst into a muffle furnace, and then heat it to 360-450° C. at a heating rate of 1-3° C. / min, calcine at a constant temperature for 12-18 hours, and then naturally cool it to room temperature to obtain a finished copper-based catalyst.
2. The method for preparing a copper-based catalyst for preparing methanol by hydrogenation of carbon dioxide according to claim 1, characterized in that: The particle size of the 13X molecular sieve powder is 1-8 μm, and the internal pore size is 0.3-0.6 nm; In the impregnation loading step and the secondary impregnation loading step, the mixed aqueous solution of copper nitrate, zinc nitrate, bismuth nitrate and molybdenum nitrate, wherein the mass ratio of copper nitrate, zinc nitrate, bismuth nitrate, molybdenum nitrate and deionized water is 30~70:10~40:4~15:1~10:150~250.
3. The method for preparing a copper-based catalyst for preparing methanol by hydrogenation of carbon dioxide according to claim 1, characterized in that: The zirconium phosphate is in powder form with a particle size of 30 to 800 nm; The particle size of the calcium oxalate powder is 0.01-0.6 μm; The particle size of the pseudo-boehmite is 10-500 nm; The particle size of the magnesium aluminum silicate is 0.1-2 μm; The feeding mass ratio of the 13X molecular sieve powder loaded with copper, zinc, bismuth and molybdenum, zirconium phosphate, calcium oxalate powder, pseudo-boehmite, deionized water and magnesium aluminum silicate is 55-95:5-12:5-11:9-16:80-130:1-5.
4. The copper-based catalyst for preparing methanol by hydrogenation of carbon dioxide prepared by the preparation method according to any one of claims 1 to 3, characterized in that: The copper-based catalyst has an initial performance of a CO2 conversion rate of 35.9-36.7%, a methanol selectivity of 95.7-96.4%, and a methanol space-time yield of 1.78-1.85 g / h / mL; and a heat-resistant performance of a CO2 conversion rate of 35.1-36.2%, a methanol selectivity of 95.1-95.9%, a methanol space-time yield of 1.74-1.80 g / h / mL; and a hydrothermal stability of 96.7-97.8%.
Citation Information
Patent Citations
Preparation method of copper-zinc-based catalyst for preparing methanol by virtue of CO2 hydrogenation
CN104437510A
Copper-based catalyst for preparing methanol through hydrogenation of carbon dioxide and preparation method of copper-based catalyst
CN117085689A
Catalyst for preparing 1,2-propylene glycol by glycerinum hydrogenation and preparation method thereof
CN103657730A
Catalyst suitable for large-scale methanol synthesis device, and preparation method thereof
CN106732616A